Merana Shanti: A Vocal Music Composition | Merana Shanti: Sebuah Komposisi Musik Vokal - Wijananda, I Made Rai wawan Sukma (GHURNITA: Jurnal Seni Karawitan, 2024)
The musical work "Merana Shanti" is an innovation in musical art combining Cak, Gongseng, and Punggalan Barong. The composer aims to create new works by exploring vocal work as the primary medium for creating passion and expanding the repertoire of vocal musical instruments. The focus is on developing vocal musical compositions that respect tradition and innovate. The method used in making this work follows the stages of the creative process outlined in the book "The Creative Process" by Brewster Ghiselin, which adopts Roger Session's creation method. The process is divided into three stages: Inspiration, Conception, and Execution. The results of the creation of this work include an interpretation of the meaning of "Merana" and "Shanti," as well as processing the elements of Cak, Punggal Barong, and Gongseng in a creative context. The use of vocals as the primary medium was chosen based on the need for exploration in the vocal realm, with the addition of Punggal Barong and Gongseng to create new nuances in vocal musical performance. In doing the work, the artist will arrange the verbal preparations carefully and in detail using patterns such as Cecandetan and Pupuh songs to produce a charming composition. "Merana Shanti" is a vocal musical composition based on the art of Cak Bona with the addition of Punggal Barong and Gongseng. The use of vocals as the primary medium was chosen to explore the possibilities of expression in this work. The artist will process the vocals with patterns such as Cecandetan and Pupuh songs, combining them with additional Punggal Barong and Gongseng instruments to create an innovative and stunning work.